Characteristic analysis of clinical trials for new traditional Chinese medicines in mainland China from 2013 to 2021 - Zhou, Yinghong; Yang, Juan; He, Yingchun; Lv, Yinghua; Wang, Chunli; Deng, Hongyong; Huang, Jihan (Frontiers in Medicine, 2022)
Objective: On the basis of the clinical trials registered on the platform for the registry and publicity of clinical drug trials of the National Medical Products Administration (NMPA), the registration and approval of clinical trials of traditional Chinese medicines (TCMs) in mainland China from 2013 to 2021 were reviewed. Method: Clinical trials of new TCMs published in Chinese were retrieved from the platform for the registry and publicity of clinical drug trials. The number of registered trials and approved trials, status of clinical trials, therapeutic area of clinical trials for the treatment of diseases, type of trial design, sample size, sponsors, and leading clinical trial center were evaluated. Results: From 2013 to 2021, a total of 965 clinical trials of new drugs applied in TCM were registered on the aforementioned NMPA platform, comprising 117 phase I trials, 586 phase II trials, 174 phase III trials, 40 phase IV trials, and 48 other clinical trials. The treatment fields included the respiratory system, alimentary tract and metabolism, genetic system and reproductive hormones, and cardiovascular system. Among the 760 phase II and phase III trials, 98.9% were randomized, 95.4% were double blind, and 98.2% were parallel controlled trials, and the proportion of placebo-controlled trials increased year by year from 2013 to 2022. From 2013 to 2021, 123 new TCMs were approved in mainland China. Conclusion: From 2015 to 2021, the number of registered clinical trials of new TCMs remained low. The approval rate was also low, but clinical trial design was greatly improved.